Utilizing Kitchen Waste as Evidence of Love for the Planet - Aziz Atmadipraja (IAIN Ternate, 2021)
This program is an empowerment for mothers in Pangandaran Regency in order to take advantage of unused organic kitchen waste to be useful for the environment. Before starting kegiatam, the group goes through several stages, including group discussions about partner activities, learning material about eco enzymes in partners, then after that we can empower the targets that have been set through the results of group discussions. Because during the Covid 19 pandemic. Nevertheless, the target remains enthusiastic in following this activity. Keywords: Eco enzyme, Love planet